2012
DOI: 10.3133/ofr20121128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil-gas and groundwater contamination at the Gibson Road landfill, Fort Gordon, Georgia, 2011

Abstract: Gibson Road Landfill The Gibson Road landfill is an approximately 35-acre site located on the southern sides of Gibson Road and Sawmill Road (unpaved) and occupies a topographically high area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For both open and closed landfills, continual monitoring is necessary for maintaining safe operations and avoiding risks, such as structural collapse due to compaction. The USGS assessed the soil-gas and groundwater contamination levels for the Gibson Road Landfill in Fort Gordon (Falls et al 2012). They found that volatile and semivolatile organic compounds, as well as polycyclic aromatic hydrocarbons, were contaminating the soil-gas and groundwater.…”
Section: Landfill Monitoringmentioning
confidence: 99%
“…For both open and closed landfills, continual monitoring is necessary for maintaining safe operations and avoiding risks, such as structural collapse due to compaction. The USGS assessed the soil-gas and groundwater contamination levels for the Gibson Road Landfill in Fort Gordon (Falls et al 2012). They found that volatile and semivolatile organic compounds, as well as polycyclic aromatic hydrocarbons, were contaminating the soil-gas and groundwater.…”
Section: Landfill Monitoringmentioning
confidence: 99%